Socialism and Axiological Formation of Personality - NevmerzhytskaОlena (Pedagogical Discourse, 2014)
The impact of the ideology of socialism on the formation of personal values is analyzed in the article. It is mentioned that these ideas, being the ideological foundations of social system, were often distortedly treated. In the process of development they have undergone the transformation from Marxism to Marxism and Leninism and then to Stalin’s totalitarianism. As a result of analysis of some sources, including archival ones, it is proved that each of these stages had different social order and educational values: 1) the intellectually and physically developed personality with materialistic world outlook, who was able to put revolutionary ideas into practice was the ideal of education in Marxist ideology; 2) the ideal of Bolshevist education was flaming and firm revolutionary with developed class consciousness, who followed the values of serving to the ideas, rank activity, belief to the bright future, diligent, patriotism, optimism, etc.; 3) the ideal of Soviet education in the period of totalitarian state making was a person of socialist labour, an educated and skilled citizen, who followed communist morality with priority of interests of socialist society, socialist Motherland as a leading principle.